If š‘Ž āƒ— ≠ 0 āƒ—, š‘Ž āƒ—. š‘ āƒ— = š‘Ž āƒ—. š‘ āƒ—, š‘Ž āƒ— × š‘ āƒ— = š‘Ž āƒ— × š‘ āƒ— , then show that š‘ āƒ— = š‘ āƒ—.

Slide30.JPG

Slide31.JPG

Learn in your speed, with individual attention - Teachoo Maths 1-on-1 Class


Transcript

Question 9 If š‘Ž āƒ— ā‰  0 āƒ—, š‘Ž āƒ—. š‘ āƒ— = š‘Ž āƒ—. š‘ āƒ—, š‘Ž āƒ— Ɨ š‘ āƒ— = š‘Ž āƒ— Ɨ š‘ āƒ— , then show that š‘ āƒ— = š‘ āƒ—. Given that š’‚ āƒ—. š’ƒ āƒ— = š’‚ āƒ—. š’„ āƒ— Now, š‘Ž āƒ—. š‘ āƒ— = š‘Ž āƒ—. š‘ āƒ— š‘Ž āƒ—. š‘ āƒ— āˆ’ š‘Ž āƒ—. š‘ āƒ— = 0 š’‚ āƒ—. (š’ƒ āƒ— āˆ’ š’„ āƒ—) = 0 Thus, either (š’ƒ āƒ— āˆ’ š’„ āƒ—) = šŸŽ āƒ— Or š’‚ āƒ— is perpendicular to (š’ƒ āƒ— āˆ’ š’„ āƒ—) š’‚ āƒ— Ɨ š’ƒ āƒ— = š’‚ āƒ— Ɨ š’„ āƒ— Now, š‘Ž āƒ— Ɨ š‘ āƒ— = š‘Ž āƒ— Ɨ š‘ āƒ— š‘Ž āƒ— Ɨ š‘ āƒ— āˆ’ š‘Ž āƒ— Ɨ š‘ āƒ— = šŸŽ āƒ— š’‚ āƒ— Ɨ (š’ƒ āƒ— āˆ’ š’„ āƒ—) = šŸŽ āƒ— Thus, either (š’ƒ āƒ— āˆ’ š’„ āƒ—) = šŸŽ āƒ— Or š’‚ āƒ— is parallel to (š’ƒ āƒ— āˆ’ š’„ āƒ—) Since š‘Ž āƒ— cannot both be perpendicular and parallel to (š‘ āƒ— āˆ’ š‘ āƒ—) Therefore, the only other solution is (š‘ āƒ— āˆ’ š‘ āƒ—) = 0 āƒ— š’ƒ āƒ— = š’„ āƒ— Hence proved

Ask a doubt
Davneet Singh's photo - Co-founder, Teachoo

Made by

Davneet Singh

Davneet Singh has done his B.Tech from Indian Institute of Technology, Kanpur. He has been teaching from the past 13 years. He provides courses for Maths, Science, Social Science, Physics, Chemistry, Computer Science at Teachoo.